Patent analysis for medicines and biotherapeutics in trials to treat COVID-19 - Srividya Ravi (South Centre, 2022)
This report provides an analysis of patents covering medicines in trials to treat COVID-19. The aim of the report is to support national patent offices and interested parties in developing countries with information that can serve as guidance for the examination of the claims contained in relevant patents or patent applications. The medicines considered for the patent analysis in this report are remdesivir, ruxolitinib, favipiravir, molnupiravir and nirmatrelvir, and the biotherapeutics tocilizumab, siltuximab and sarilumab.
Keywords: 300; Access to Medicines; Affordable Medicines; Biotherapeutics; Coronavirus; COVID-19; Favipiravir; Global Health; Health; Intellectual Property; Molnupiravir; Nirmatrelvir; Pandemic; Patent; Patent Offices; Public Health; Remdesivir; Ruxolitinib; Sarilumab; Siltuximab; Tocilizumab